Mummies in the Morning (First stepping stone bk, ,, 1994)
Annie and Jack find themselves transported back in time to ancient Egypt, where they encounter a dead queen and her thousand-year-old mummy.

Civil War on Sunday (Magic tree house, 21,, 2000)
Jack and Annie are transported by their magic tree house to the time of the Civil War where they meet Clara Barton.

Revolutionary war on Wednesday (Magic tree house, 22,, 2000)
Using their magic tree house, Jack and Annie travel back to the time of the American Revolution and help General George Washington during his famous crossing of the Delaware River.

Blizzard of the blue moon (Magic tree house, 36,, 2006)
The magic tree house carries Jack and Annie to New York City in 1938 on a mission to rescue the last unicorn.

Balto of the Blue Dawn (Magic tree house.Merlin mission, 54,, 2016)
"Jack and Annie travel back in time to 1925 Nome, Alaska, where they meet Balto, the famous sled dog, and help save the town from illness"--

The knight at dawn (First stepping stone bk, ,, 2006)
Eight-year-old Jack and his younger sister Annie use the magic treehouse to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.

Shadow of the shark (Magic tree house. A Merlin mission, 25,, 2015)
As a thank-you from Merlin and Morgan, Jack and Annie are sent on what should be a vacation at a luxurious resort in Cozumel, Mexico, but is, by mistake, an adventure with ancient Mayans, instead.

Night of the ninth dragon (Magic tree house. A Merlin mission, 55,, 2016)
"When a mysterious note invites them to Camelot, Jack and Annie travel in the magic tree house to the magical kingdom where they must find a lost dragon"--

Night of the new magicians (Magic tree house, 35,, 2007)
Jack and Annie visit the Paris World's Fair of 1889 in an effort to protect four scientific pioneers from an evil sorcerer.

A big day for baseball (Magic tree house, 29,, 2019)
"Jack and Annie use the magic tree house to travel back in time to 1947 Brooklyn, New York, where they pretend to be batboys at Jackie Robinson's first game with the Brooklyn Dodgers against the Boston Braves"--

Narwhal on a sunny night (Magic tree house, 33,, 2021)
"The magic tree house whisks Jack and Annie away to Greenland where they discover they've traveled back in time to meet Lief Erikson"--Provided by publisher.